PENGARUH PEOPLE, PROCESS, DAN PHYSICAL EVIDENCE TERHADAP KEPUTUSAN MENABUNG DI BANK SYARIAH - RONI ANDESPA; RANGGA WISANGGARA; FAZNIL HUSNA S. RASYAD; RIANDY MARDHIKA ADIF (Maqdis: Jurnal Kajian Ekonomi Islam, 2019)
The research theme is "Islamic Bank Management". The research objective was to see the effect of people, process, and physical evidence on the customer's decision to save in Islamic banks. The object of research is Islamic banks in West Sumatra. The study sample was 250 customers. Research is causality. The research method is quantitative. The results of the study are: 1) People significantly influence saving decisions, 2) Process significantly influences saving decisions, 3) Physical evidence significantly influences saving decisions.